Antidiarrheal, antimicrobial and antioxidant potentials of methanol extract of Colocasia gigantea Hook. f. leaves: evidenced from in vivo and in vitro studies along with computer-aided approaches - Safaet Alam; Mohammad A. Rashid; Md. Moklesur Rahman Sarker; Nazim Uddin Emon; Mohammad Arman; Isa Naina Mohamed; Mohammad Rashedul Haque (BMC, 2021)
Abstract Background Colocasia gigantea, locally named as kochu is well-known due to its various healing power. This research is to investigate the antidiarrheal, antimicrobial and antioxidant possibilities of the methanol soluble extract of Colocasia gigantea. Methods The antidiarrheal investigation was performed by using in vivo castor oil-induced diarrheal method whereas in vitro antimicrobial and antioxidant investigation have been implemented by disc diffusion and DPPH scavenging method respectively. Moreover, in silico studies were followed by molecular docking analysis of several secondary metabolites that were appraised with Schrödinger-Maestro v11.1 and Biovia Discovery Studio. Results The induction of plant extract (200 and 400 mg/kg, b.w, p.o) has minimized the castor oil mediated diarrhea by 16.96% (p < 0.01) and 38.89% (p < 0.001) respectively compared to control group. The methanol extract of C. gigantea showed mild sensitivity against almost all the tested strains but it shows high consistency of phenolic content and yielded 67.68 μg/mL of IC50 value in the DPPH test. In the PASS prediction, selected isolated compounds have demonstrated significant antidiarrheal and antimicrobial activity following the Lipinski drug rules which have ascertained efficacy with the compounds in molecular docking study. Conclusion The results of this scientific research reflects that the methanol soluble extract of C. gigantea is safe and may provide possibilities of alleviation of diarrhea along with being a potential wellspring of antioxidant and antimicrobial agents which can be considered as an alternate source for exploration of new medicinal products in near future.